A New Interpretation of Apparent Induction Period in Ring‐Opening Polymerization of Octamethylcyclotetrasiloxane in Acid Emulsion. Issue 1 (28th October 2020) - Suzuki, Kiyoshi; Totsuka, Takahiro; Ishiguro, Daisuke; Okubo, Shun; Tobita, Hidetaka
Abstract: A following new interpretation of apparent induction period is proposed considering the experimental results obtained: octamethylcyclotetrasiloxane (D4) is activated by the reaction with acid to generate an activated derivative (A4). A4 reacts with D4 to generate A8, an active species containing eight dimethylsiloxane units. A8 backbites to generate mostly A4 and D4, which causes retardation in polymerization, but occasionally to form A3 and D5. A3 is highly reactive, and when the concentration of A3 exceeds a certain limit, much A i where i is large enough is formed and promotes fast growth of chain at the interfacial area due to high concentration of D4. The interpretation assumes that A3 accelerates growth of chain faster than other species, and that A8 tends to backbite rather than grow. The interpretation is supported by the experimental results of polymerization conducted with D4 and D3, or D5 and D3 charged. Abstract : Hexamethylcyclotrisiloxane (D3) and its derivative are indicated to be the main components accelerating the ring‐opening polymerization (ROP) of cyclomethicones such as D4 in acid emulsion. Addition of a small amount of D3 significantly shortens the apparent induction period of the ROP of D4. The high probability of backbiting reaction of activated D8 is also indicated.